THU0198 Immunogenicity associated with a transition from adalimumab reference product to abp 501 in patients with rheumatoid arthritis. (12th June 2018) - Krishnan, E.; Mytych, D.; Zhang, N.; Wang, H.; Kaliyaperumal, A.
Abstract : Background: In clinical practice, patients treated with an originator product may be transitioned to a biosimilar. Therefore, it is important to ensure that such transition is safe and is not associated with increased immunogenicity. Objectives: To study the incidence of binding anti-drug antibodies (bADAs) and neutralising anti-drug antibodies (nADAs) after patients with rheumatoid arthritis (RA) are transitioned from adalimumab reference product (RP) to ABP 501, an approved biosimilar for adalimumab. Methods: We analysed data from the open-label extension (OLE) of a randomised 26 week phase 3 study (NCT 01970475) comparing ABP 501 and adalimumab. In this OLE study (NCT02114931 ), patients originally randomised to ABP 501 in the parent study continued on ABP 501 while patients originally randomised to adalimumab (RP) were switched to ABP 501 so that all patients received ABP 501. Specifically, we studied the incidence of new ADAs in patients who were ADA negative at the time of entry into the OLE study. The incidence after excluding transiently elevated ADAs was also examined. Results: The Table summarises the incidence of ADAs. Conclusions: Transitioning from adalimumab reference product to ABP 501 was not associated with increased immunogenicity over the observational period of 72 weeks. Disclosure of Interest: E. Krishnan Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Mytych Shareholder of: Amgen Inc., Employee of: Amgen Inc., N. Zhang Shareholder of: Amgen Inc., Employee of: Amgen Inc., H. Wang Shareholder of: Amgen Inc., Employee of: Amgen Inc., A. Kaliyaperumal Shareholder of: Amgen Inc., Employee of: Amgen Inc.